Media Convergence Strategy on Metro TV: Optimizing the Use of New Media in the OPSI Program - Maulianza, Medo; Ariestyani, Arleen; Ahdareni, Riana Jogi; Aprilianti, Limia (CHANNEL: Jurnal Komunikasi, 2022)
This study aims to determine Metro TV's media strategy in media convergence, especially in optimizing the use of new media for broadcast programs: "OPSI." This study describes how the media implements the use of social media for the development of tv programs. The method in this study uses descriptive qualitative with in-depth interviews and observations. Metro TV seeks to optimize the advantages of new media for media convergence to broadcast in a multiplatform way. These advantages include multimedia, topicality, fastness, update, flexibility, breadth, and interaction. It is used to expand the reach and adapt to the audience's habits in consuming media today. Moreover, it can be used as a medium for promotion before the program airs.